Role of the Mucin-2 and Kaiso genes in the social behavior of mice - E. N. Kozhevnikova; K. M. Achasova; V. S. Korostina; E. B. Prokhortchouk; E. A. Litvinova (Вавиловский журнал генетики и селекции)
Inflammatory processes in the gut lead to abnormalities in various systems of the body, in particular, to changes in the activity of the central nervous system. Although the mechanisms of these effects are not yet known, it has been demonstrated that intestinal inflammation is associated with anxiety and depression. In this work, we used an animal model of intestinal inflammation, which might result in behavioral changes. The animals used were knock-out mice with double mutations in the Kaiso and Mucin-2 genes. The Kaiso gene encodes a transcription factor that is expressed both in the brain and in the intestine. The Mucin-2 gene encodes a protein that serves as a scaffold for the synthesis of intestinal proteoglycan. Mucin-2 is a major proteoglycan of the intestinal mucus layer and performs multiple functions, including barrier and defensive ones. We used knock-out animals with a mutation in the transcription factor Kaiso in tests assessing social behavior, but did not observe any difference between test subjects and wild-type animals. By contrast, double knock-out animals that additionally had a mutation in Mucin-2, a major gene for intestinal proteoglycan, displayed significant changes in social behavior: lower aggression rates and higher rates of courtship behavior toward a male intruder. These results suggest that intestinal homeostasis might have a strong impact on the nervous system of the animals. It remains unclear whether the influence of the two genes is synergistic or the knock-out of the Mucin-2 gene alone determines this behavior in mice. Further investigations will help clarify the matter.